2018
DOI: 10.1177/1559325818789845
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Whole-Body Exposure to Low-Dose Radiation Combined With Topical Application of Basic Fibroblast Growth Factor and Zinc Accelerates Wound Healing in Diabetic Rats

Abstract: We reported the acceleration of skin wound healing in diabetic rats by repeated exposure to low-dose radiation (LDR). Here, we explored whether the wound healing could be further improved when LDR was combined with a topical application of basic fibroblast growth factor (bFGF) or zinc. Wounds were established on the backs of type 1 diabetic rats induced by a single injection of streptozotocin. Rats were treated daily with normal saline (Diabetes), LDR, bFGF, zinc, or combined 3 treatments for 5 consecutive day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The low-dose radiation combined with topical application of fibroblast growth factor and zinc accelerated wound healing of skin lesions in diabetic rats resulting in more organized collagen fibers, faster wound closure and epithelialization 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The low-dose radiation combined with topical application of fibroblast growth factor and zinc accelerated wound healing of skin lesions in diabetic rats resulting in more organized collagen fibers, faster wound closure and epithelialization 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have examined the effect of low-dose radiation on diabetic complications. [37][38][39] One of the most serious complications is diabetic cardiomyopathy, characterized by cardiac remodeling that includes cardiac hypertrophy and prefrontal changes. It is related to cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A superior effect on wound healing in the LDR-bFGF-zinc combination group was observed in any of these independent treatment groups. 38 As a mechanism of this effect, they found that repeated irradiations of 75 mGy X-rays (LDR) increased the proportion of CD31 þ / CD3 þ stem cells in the bone marrow and circulation, and induced vascular regeneration, cell proliferation, and the expression of matrix metalloproteinase-2 (MMP-2). It is presumed that the expression of MMP-9 was promoted, and the skin wound healing in diabetes was significantly promoted.…”
Section: Discussionmentioning
confidence: 99%
“…Zn 2+ was also reported to induce human skin fibroblasts (HSFs) to differentiate into myofibroblasts thus promoting wound healing . When combined with bFGF, they showed synergistic therapeutic effects on wound healing in diabetic rats …”
Section: Introductionmentioning
confidence: 99%